2017
DOI: 10.1021/acsami.7b11062
|View full text |Cite
|
Sign up to set email alerts
|

Strong Near-Infrared Absorbing and Biocompatible CuS Nanoparticles for Rapid and Efficient Photothermal Ablation of Gram-Positive and -Negative Bacteria

Abstract: Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) are the most common infectious bacteria in our daily life, and seriously affect human's health. Because of the frequent and extensive use of antibiotics, the microbial strains forming drug resistance have become more and more difficult to deal with. Herein, we utilized bovine serum albumin (BSA) as the template to synthesize uniform copper sulfide (CuS) nanoparticles via a biomineralization method. The as-prepared BSA-CuS nanocomposites showed go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
108
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(112 citation statements)
references
References 58 publications
3
108
0
Order By: Relevance
“…In addition to NO, nanomaterial‐based photothermal therapy is recognized as a promising way for combating bacterial infections . The photoconversion nanomaterials are able to absorb light, especially the near‐infrared light and release it as heat, causing the elevation of the local temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to NO, nanomaterial‐based photothermal therapy is recognized as a promising way for combating bacterial infections . The photoconversion nanomaterials are able to absorb light, especially the near‐infrared light and release it as heat, causing the elevation of the local temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[ 71,220,221 ] This absorbed energy can be dissipated either by re‐emitting a photon, or via heat through electron–electron interactions and then electron–phonon relaxation, which induces vibrations in the metal lattice structures, these lattice vibrations are transferred into thermal energy causing localized heat around the nanomaterial [ 44,71,220 ] ( Figure ). This phenomenon has been predominately studied using gold; however silver, [ 222 ] copper, [ 223 ] and other materials [ 224 ] have also been investigated. By conjugating specific attachments to the nanomaterials, such as antibodies, they can specifically target the pathogen of interest, where the localized increase in temperature causes cell death through a suite of actions including denaturation of essential proteins/enzymes, induction of heat shock proteins, disruption of metabolic signaling and rupture of the cell membrane [ 71,85,218,219,225–227 ] (Figure 10).…”
Section: Light‐activated Antimicrobial Metal Nanomaterialsmentioning
confidence: 99%
“…Reproduced with permission. [ 223 ] Copyright 2017, ACS Publications. F) Anti‐salmonella‐antibody‐conjugated oval‐shaped gold nanoparticles.…”
Section: Light‐activated Antimicrobial Metal Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Copper sulfide a cheaper alternative when conjugated with bovine serum albumin showed no killing activity in antibacterial tests for Staphylococcus aureus and Escherichia coli. However, after NIR exposure, the nanocomposite at low concentration exhibited strong NIR irradiation absorbance and can be used as an efficient photothermal conversion agent for bacteria ablation (80%) with a 980 nm laser within 10 min [56]. Tong et al (2018) reported that the nanocomposite of DNA with Ag-nanoparticles and Graphene (ssDNA-AgNPs@GO) presented larger activity against Gram-positive and Gram-negative bacteria with low MIC compared to ssDNA-Ag-nanoparticles and GO alone [57].…”
Section: Biomolecules Functionalized Nanoparticlesmentioning
confidence: 99%